5 modern Japanese novelists = Five modern Japanese novelists - Keene, Donald 1922-2019 (Columbia University Press, 2003)
"Five Modern Japanese Novelists profiles five prominent writers whom Donald Keene knew personally: Tanizaki Jun'ichiro, Kawabata Yasunari, Mishima Yukio, Abe Kobo, and Shiba Ryotaro. Keene masterfully blends vignettes describing his personal encounters with these famous men with autobiographical observations and his trademark learned literary and cultural analysis."--BOOK JACKET.